2011
DOI: 10.1007/s00213-011-2349-6
|View full text |Cite
|
Sign up to set email alerts
|

Subjective, psychomotor, and physiological effects of oxycodone alone and in combination with ethanol in healthy volunteers

Abstract: In this study, 10 mg of oral oxycodone combined with a low dose of ethanol generated abuse liability-related effects, but when tested separately, they did not. Further psychopharmacological investigations of this combination are warranted in light of these findings and the fact that nonmedical use of prescription opioids is sometimes accompanied by use of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…There were two different time points in the session when capsules were given because in the session when we tested the effects of 75 mg pregabalin in combination with 10 mg oxycodone, we wanted to measure their effects when the drugs were both close to, or at, their peak effects. In a preliminary pilot study we noted that the psychoactive effects of pregabalin tended to peak two hours after its administration, and prior studies with 10 mg oxycodone conducted in our laboratory indicated peak effects one hour after its administration (Zacny and Gutierrez, 2011; Zacny and Lichtor, 2008). …”
Section: Methodsmentioning
confidence: 77%
“…There were two different time points in the session when capsules were given because in the session when we tested the effects of 75 mg pregabalin in combination with 10 mg oxycodone, we wanted to measure their effects when the drugs were both close to, or at, their peak effects. In a preliminary pilot study we noted that the psychoactive effects of pregabalin tended to peak two hours after its administration, and prior studies with 10 mg oxycodone conducted in our laboratory indicated peak effects one hour after its administration (Zacny and Gutierrez, 2011; Zacny and Lichtor, 2008). …”
Section: Methodsmentioning
confidence: 77%
“…For example, mixing prescription stimulants and alcohol can override the protective mechanism of passing out when drinking and approaching dangerous blood-alcohol concentrations which can lead to life-threatening consequences (SAMHSA, 2006). In addition, there is evidence that alcohol increases the subjective effects (e.g., drug liking and euphoria) of prescription opioids, which may partially explain why alcohol and prescription opioids are often simultaneously co-ingested (Zacny and Gutierrez, 2011). Notably, central nervous system depressants (e.g., prescription opioids, sedatives and tranquilizers) are much more toxic and associated with more severe consequences when they are taken with other drugs that depress the central nervous system, such as alcohol, as compared to when they are taken alone (Cone et al, 2004; McCabe et al, 2006; SAMHSA, 2014).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Increases in positive subjective effects (eg, “drug liking,” “take again,” “pleasant body sensations”) have been reported by healthy volunteers administered a combination of oxycodone (10 mg) and ethanol (0.3 or 0.6 g/kg) compared with when they received either substance alone (Figure 5). 47 Psychomotor and cognitive performances were not affected by any of the active drug scenarios.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 92%